Loss of Blood Group Antigens in Haematolymphoid Malignancy: A Case Series from a Cancer Institute from Northeast India - Sarma, Ranjita; Kuli, Karabi; Kalita, Chandana; Iqbal, Asif; Gupta, Sakshi (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: Altered expression of blood group antigens has been reported in association with both solid and hematological malignancies. This alteration usually results from genetic mutations leading to incomplete or abnormal synthesis of antigens. Transitional loss of red blood cell (RBC) antigens, particularly from the ABO system, is most commonly observed in hematological malignancies, causing blood group discrepancies that often reverse to the patient’s historical blood group during remission. Loss of A and B antigens has also been associated with lung, bladder, and colon cancers. However, limited data is available regarding hematological malignancies. Materials and methods: This retrospective review of blood group discrepancies (forward grouping) was conducted on patients admitted for hematolymphoid malignancies at our institute over a 3.5-year period (March 13, 2020, to September 12, 2023). Blood grouping, initially performed using the column agglutination test, was repeated using the conventional tube method. Further confirmation of the blood group was performed using saliva tests and adsorption-elution tests as indicated. Detailed patient histories were collected from hospital records and analyzed. Results: A total of seven patients presented with either loss or decreased expression of blood group antigens. The most common diagnosis was acute myeloid leukemia (AML) with FLT3 mutation, and the most frequently affected antigen was A. Conclusion: Hematolymphoid malignancies are associated with loss of blood group antigens, leading to blood group discrepancies. Blood transfusion is a crucial component of supportive care for these patients. Therefore, proper workup of blood group discrepancy cases should be conducted and documented to prevent delays in blood transfusion.